PENGAWASAN PENJUALAN MAKANAN DAN MINUMAN KEMASAN DI KOTA MEMPAWAH KABUPATEN PONTIANAK - Nugroho E.01108123, Adhityo (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title of this article is the Sales Supervision Food and Beverage Packaging In the city of Pontianak regency Mempawah. Supervision of food and beverage sales in the city Mempawah done is one of the government efforts in surveillance and consumer protection. The high intensity often found selling illegal products, the packaging is damaged and Out of date. Writing this article is intended to provide an overview of how the oversight of market participants selling food and beverage packaging products directly and indirectly, and that influence has not been optimal control in the city of Pontianak regency Mempawah. The results of this study indicate that the surveillance conducted was minimal and has not been able to reach a whole In the City Mempawah.Keywords: Food and Beverage Packaging, Monitoring Direct and Indirect Supervision.